The Effect of Wood Tar and Molasses Composition on Calorific Value and Compressive Strength in Bio-coke Briquetting - Abrar Muharman; Anggoro Tri Mursito; Erlina Yustanti (Center of Biomass & Renewable Energy, Diponegoro University, 2022)
Biomass-based materials have the potential to replace conventional cokes for blast furnaces in the steel manufacturing study. Biomass as a renewable energy source can reduce the consumption of coking coal. The current challenge is saving fossil energy and waste management. The steelmaking industry with environmentally friendly processes and high energy efficiency is expected today. Many researchers have partially developed biomass as an alternative renewable resource to replace fossil fuels. This study aimed to determine the effect of composition the blending ratio of wood tar and molasses as a binder on the calorific value and compressive strength of bio-coke. The carbonization of redwood waste to produce high-quality charcoal was carried out at 500 °C with a kiln rotation speed of 20 rpm and a slope of 5°. The resulting charcoal showed a promising result with a 23.87 MJ/kg calorific value. The carbonization process of the redwood increased the fixed carbon value by up to 130% and the calorific value by 40%. The second part of this study focuses on bio-coke production by blending coking coal with redwood charcoal at 90:10 wt%. The coking coal and the redwood charcoal particle sizes were 40 and 50 mesh, respectively. A 15 wt% binder was added to increase the compressive strength of the bio-coke. The binder composition ratios of molasses: wood tar were 15:0, (12.5:2.5), and 10:5 wt%. The briquette was pressed using a cylinder die with a height: diameter ratio of 2.7:5.0 cm, then compacted up to 20 MPa followed by heating at 1100 °C for four hours. The bio-coke with a binder composition of 2.5 wt% wood tar + 12.5 wt% molasses produced a compressive strength of up to 5.57 MPa with a sulfur content of 0.8 wt% and produced a calorific value of 31.25 MJ/kg with an ash content of 9.6%. The study showed that the bio-coke produced meets some requirements for steelmaking industry.